2020
DOI: 10.1055/s-0040-1713668
|View full text |Cite
|
Sign up to set email alerts
|

Perforator Variability of the Anterolateral Thigh Flap Identified on Computed Tomographic Angiography: Anatomic and Clinical Implications

Abstract: Abstract Background The anterolateral thigh (ALT) flap is a useful flap with minimal donor site morbidity. Preoperative computed tomographic angiography (CTA) for lower extremity reconstruction can determine vessel integrity and plan for recipient vascular targets. This study reviews lower extremity CTAs to further characterize ALT vascular anatomy and associated clinical implications thereof. Patients and Methods Lower extremity CTA studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
(54 reference statements)
1
19
0
Order By: Relevance
“…This muscle represents the largest component of the quadriceps femoris, and functional loss is more likely if greater than half the muscle is sacrificed. 22,[24][25][26] At worst, if the ALT cannot be salvaged or successfully converted, it could lead to total flap failure. Preoperative CTA minimizes the risk of encountering these undesirable scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This muscle represents the largest component of the quadriceps femoris, and functional loss is more likely if greater than half the muscle is sacrificed. 22,[24][25][26] At worst, if the ALT cannot be salvaged or successfully converted, it could lead to total flap failure. Preoperative CTA minimizes the risk of encountering these undesirable scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Another secondary benefit of preoperative imaging is that it provides an appraisal of predicted flap thickness. 6,18,22 The ALT can demonstrate significant variation in subcutaneous fat based on body habitus and ethnic and regional populations. 18,27 This is a factor that must be considered in flap design, and thus as the subcutaneous tissue becomes significantly thinner with distal progression, perforators can be actively selected based on subcutaneous course and corresponding reconstructive needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 From this point of view, free osseous myocuta-neous flap was not considered the best choice for reconstruction after maxillary malignant tumor resection.The scar of ALTF has minimal impact on the function of the donor site compared with other free flaps. 28 In addition, ALTF is superior in terms of being an adequately sized flap, sparing major vasculature, and having better cosmesis at both donor and recipient sites. 29 Other studies reported that the donor site complications of the anterolateral thigh valve are rare compared with radial forearm free flap.…”
mentioning
confidence: 99%
“…The CTA offers the advantage of improved perforator location sensitivity and specificity, but this technique does have contrast and radiation-related morbidity. 10 CDU is a potentially faster, cheaper option for the experienced surgeon or radiographer that also provides information related to vessel flow patterns and tissue characteristics. 11,12 Additionally, CDU offers intraoperative and postoperative flap monitoring due to its portability and vessel flow evaluation capabilities.…”
mentioning
confidence: 99%